Impacto de la erradicación del gato (felis catus), en dos roedores endémicos de la Isla Coronados, Golfo de California, México - Rodríguez-Moreno, Angel; Arnaud, Gustavo; Tershy, Bernie (Instituto de Ecología, A.C., 2007)
It is not known when the domestic cat (Felis catus) was introduced to Coronados Island or when they reached it. Their impact on endemic rodents has been evident, rodents constitute 70% of their diet and they are putting in danger the survival of rodents. Cat eradication was initiated in November 1998 and finished in March 1999. In order to identify the eventual response of rodents to the absence of cats, a monitoring program of two resident rodents Peromyscus pseudocrinitus and Chaetodipus spinatus pullus, was undertaken before, during, and after the eradication program. The monitoring program finished in 2005. Initially an increase in rodent populations occurred followed by fluctuations in the population. Despite the fact that there was no evident benefit derived from the eradication program, it is clear that their removal was positive, since their presence represented a potential risk to endemic rodent species on the island, which could be exterminated during critical periods if feral cat continued in the island.